A Closer Look at the Effect of Market Growth on Industries' Profits - Bradburd, Ralph M.; Caves, Richard E. (The Review of Economics and Statistics, 1982)
EVERYBODY talks about the relation of industries' profit rates to their markets' rates of growth, but nobody does anything about it. Specifically, researchers have confirmed the effect of the growth of nominal output on profits in many multivariate studies, without specifying closely the hypothesis under test or the measure of demand growth appropriate to test it. A profits-growth relationship could stem from several mechanisms-the lagged adaptation of capacity to unexpected changes in demand, reactions of oligopolists to disturbances in their consensus, etc. These mechanisms-how and where they work-hold their own normative interest. Therefore, knowing what behavior (and what structure, lying behind it) accounts for the profits-growth relationship should do more than improve the specifications of our studies of allocative efficiency. It should also expand our knowledge of adaptive processes that are important and hard to observe directly. In this paper we shall synthesize the available explanations of why changes in market demand should affect an industry's profits, then present a statistical test of the relative significance of the competing explanations.